2020
DOI: 10.1001/jamanetworkopen.2020.3942
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Cancer Treatment at Top-Ranked US Cancer Hospitals vs Affiliates of Top-Ranked Cancer Hospitals

Abstract: IMPORTANCE Hospital networks formed around top-ranked cancer hospitals represent an opportunity to optimize complex cancer care in the community.OBJECTIVE To compare the short-and long-term survival after complex cancer treatment at top-ranked cancer hospitals and the affiliates of top-ranked hospitals. DESIGN, SETTING, AND PARTICIPANTSThis cohort study was conducted using data from the unabridged version of the National Cancer Database. Included patients were individuals 18 years or older who underwent surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Several studies have analyzed longer-term (two-to five-year) survival of patients diagnosed with specific types of cancer (Table 2). [26][27][28][29][30][31][32] Not only is the longer-term follow-up a strength, but these studies controlled for attributes of the tumor not in claims data-for example, tumor stage, grade, depth, 30 and size 26 at initial diagnosis. These studies also tended to control for surgical procedure volume.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed longer-term (two-to five-year) survival of patients diagnosed with specific types of cancer (Table 2). [26][27][28][29][30][31][32] Not only is the longer-term follow-up a strength, but these studies controlled for attributes of the tumor not in claims data-for example, tumor stage, grade, depth, 30 and size 26 at initial diagnosis. These studies also tended to control for surgical procedure volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has further defined gaps in patient outcomes between the tertiary and community oncology settings. Boffa et al examined perioperative mortality and long‐term survival—key surgical endpoints for cancer patients—at top‐ranked tertiary centers and affiliated community sites 16 …”
Section: Discussionmentioning
confidence: 99%
“…Boffa et al examined perioperative mortality and long‐term survival—key surgical endpoints for cancer patients—at top‐ranked tertiary centers and affiliated community sites. 16 This retrospective analysis of nearly 120,000 patient cases (33% of whom were treated at affiliated community centers) concluded that perioperative mortality was higher at affiliate centers than at the tertiary centers and that long‐term survival was significantly lower at affiliate practices. Additional work from Syed et al has demonstrated that length of stay for certain urologic cancer surgeries was shorter in the tertiary setting as compared to community practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer surgery outcomes have improved during the past three decades, primarily because of the advancements made in surgery, anaesthesia, surgical technology, perioperative, and critical care domains. 3,4 Operative mortality in patients receiving complex cancer surgeries such as Whipple's resection and oesophagectomy has reduced drastically. 5 However, most of these studies originate from tertiary care cancer centres in high-income countries, and there is little literature available related to cancer surgical outcomes from LMICs.…”
Section: Do Hospital Facilities Influence Global Cancer Surgery Outco...mentioning
confidence: 99%